Formation of Instantaneous Differential and Restraining Cur-rents for Differential Protection of Busbar Assemblies - V. S. Kachenya; M. S. Loman (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2020)
The methods of forming differential and restraining currents for busbar differential protection are reviewed; their advantages and disadvantages are considered. It is noted that differential protection according to instantaneous values has a shorter proper response time than for current ones, since it does not use digital filters. The response characteristic and principles of setting selection are studied. The effect of sampling on the operation of differential protection according to instantaneous values is analyzed. It was found that without the use of special measures, depending on the sampling step and the frequency of the signal, the response current would fluctuate within the mathematical error caused by sampling. A solution to this problem has been proposed. The method consists in applying piecewise quadratic interpolation and determining the values of inflection points of instantaneous differential and restraining current signals. The efficiency of the proposed method has been evaluated. It was found that its use reduces the error in determining the response current. For a sinusoidal signal, the maximum possible error was 0.02 %. The trajectories of operating point s of differential protection in case of external fault with saturation of current transformers have been analyzed. In this mode, protection for instantaneous values is more susceptible to false positives than for active ones. The method of exponential smoothing of the restraining current was considered and investigated. An exponential smoothing algorithm has been proposed and analyzed. It is concluded that exponential smoothing increases the stability of the differential protection according to instantaneous values to external faults. Exponential smoothing does not exclude the possibility of false positive of differential protection in case of external fault.